The use of a rating instrument to teach and assess communication skills of health-care workers in a clinic in the Western Cape - M Steyn (AOSIS, 1999)
Research in health communication shows communication to be an important aspect of successful health-care. Moreover, training courses which provide feedback have been shown to improve health professionals' ability to conduct successful interviews. This article describes a rating instrument which was developed in order to facilitate teaching and assessing the communication aspects of health-care interviews. The instrument was found to be useful in a training programme offered to nursing staff of a TB Clinic in Mitchells Plain, Western Cape. The instrument appears as Table 1. In the Table categories of communication behaviours, each indicating an important aspect of the interaction, are given as the six headings.